Breaking the cycle: immune complexes, complement activation, and novel immunotherapies in lupus nephritis - Dong, Cuiting; Wu, Mingda; Liu, Haonan; Yang, Kunpeng; Ma, Shuang; Guo, Yan; Lan, Yuejiao; Lu, Xiaodan (Frontiers in Immunology, 2025)
Lupus nephritis (LN), a severe manifestation of systemic lupus erythematosus (SLE), is driven by immune complex deposition and complement activation, resulting in glomerular inflammation and podocyte injury. Beyond being passive targets, podocytes actively modulate renal immunity through cytokine secretion and antigen presentation. Recent advances in urinary biomarkers such as NGAL, TWEAK, and MCP-1 and composite indices like the Renal Activity Index for Lupus (RAIL) offer dynamic and noninvasive monitoring of disease activity. Immunotherapy has transitioned from nonspecific immunosuppression to targeted biologics, with agents such as belimumab and telitacicept improving outcomes by modulating B-cell function. Additionally, emerging therapies including bortezomib and daratumumab demonstrate efficacy in refractory LN through plasma cell depletion. This review summarizes current immunological insights, biomarker innovations, and immunotherapy strategy to support precision medicine and improve long-term renal prognosis in LN.